715 FS118, a tetravalent bispecific antibody targeting LAG-3 and PD-L1, induces LAG-3 shedding resulting in receptor downregulation by T cells via a novel mechanism of action. (10th December 2020) - Morrow, Michelle; Faroudi, Mustapha; Chakraborty, Krishnendu; Liao, Wenjia; Winnewisser, Julia; Seal, Claire; Gliddon, Daniel; Brewis, Neil
Abstract : Background: Upregulation of immune checkpoints, such as LAG-3, plays an important role in promoting resistance to anti-PD-(L)1 therapy. FS118, currently being evaluated in a Phase 1 clinical trial in patients with advanced malignancies, is a tetravalent bispecific antibody targeting LAG-3 and PD-L1 that can overcome immune suppressive signals with greater preclinical activity than a combination of monoclonal antibodies. 1 Here, we demonstrate a novel mechanism of action for FS118 in shedding of LAG-3 from the surface of T cells that is not observed with the combination of PD-L1 and LAG-3 antibodies. Methods: Human ex vivo assays were performed by co-culturing activated CD4+ T cells with iDCs in the presence of Staphylococcal enterotoxin B and FS118, or control reagents. Soluble LAG-3 was measured by ELISA from day 4 to 13. A mouse tumor model used MC38 cells implanted subcutaneously into C57Bl/6 mice. Expression of surface markers was measured on tumor-infiltrating lymphocytes (TILs) from disaggregated tumors and soluble LAG-3 was measured in serum following dosing of mice intraperitoneally with FS118 surrogate or control reagents. Soluble LAG-3 in the serum of patients treated with FS118 was measured by ELISA (Phase 1 trial NCT03440437 ). Results: In an ex vivo T cell assay, FS118 resulted in an increase in the concentration of soluble LAG-3 in the cell culture medium, an effect that was greater than with the combination of the individual bispecific components. Addition of inhibitors of either ADAM10 or ADAM17 to the FS118-treated cells resulted in a decrease in the levels of soluble LAG-3 in the cell culture medium. In MC38 tumor-bearing mice, a mouse surrogate of FS118 decreased the levels of surface LAG-3 expressed by TILs, in contrast to the combination of the bispecific components where an increase in surface LAG-3 was observed. This corresponded with an increase in soluble LAG-3 in the serum following treatment with a mouse surrogate of FS118. Finally, in patients receiving treatment with FS118, a dose dependent increase in soluble LAG-3 was detected in the blood. Conclusions: FS118 mediates LAG-3 shedding from the surface of immune cells via a mechanism that is dependent upon simultaneous binding to both PD-L1 and LAG-3. This shedding was mediated by ADAM10 and ADAM17 metalloproteinases. Removing LAG-3 from the surface of TILs via shedding may be an important mechanism by which FS118 overcomes compensatory upregulation of LAG-3 induced by PD-L1 blockade. Soluble LAG-3 may be an important biomarker for monitoring the pharmacodynamic activity of FS118 in patients. Ethics Approval: All animal experiments were conducted under a UK Home Office Project Licence and approved by an Animal Welfare and Ethical Review Board (AWERB) in accordance with the UK Animal (Scientific Procedures) Act 1986 and with EU Directive EU 86/609 Reference: Kraman M, Faroudi M, Allen N, Kmiecik K, Gliddon D, Seal C, Koers A, Wydro M, Winnewisser J, Young L, Tuna M, Doody J, Morrow M, Brewis N. FS118, a Bispecific Antibody Targeting LAG-3 and PD-L1, Enhances T-Cell Activation Resulting in Potent Antitumor Activity. Clin Cancer Res 2020;26 :3333–3344